COMPORTAMENTO DE ð˜Žð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ ð˜®ð˜¢ð˜¹ cv. Davis TRATADA COM REGULADORES VEGETAIS SOB INFESTAÃ‡ÃƒO DE ð˜Šð˜°ð˜ð˜ð˜¦ð˜µð˜°ð˜µð˜³ð˜ªð˜¤ð˜©ð˜¶ð˜® ð˜¥ð˜¦ð˜®ð˜¢ð˜µð˜ªð˜¶ð˜® f. ð˜µð˜³ð˜¶ð˜¯ð˜¤ð˜¢ð˜µð˜¢ - Castro, Paulo R. C.; Kimati, Hiroshi; Moraes, Roberto S. (REVISTA DE AGRICULTURA, 2020)
COMPORTAMENTO DE ð˜Žð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ ð˜®ð˜¢ð˜¹ cv. Davis TRATADA COM REGULADORES VEGETAIS SOB INFESTAÃ‡ÃƒO DE ð˜Šð˜°ð˜ð˜ð˜¦ð˜µð˜°ð˜µð˜³ð˜ªð˜¤ð˜©ð˜¶ð˜® ð˜¥ð˜¦ð˜®ð˜¢ð˜µð˜ªð˜¶ð˜® f. ð˜µð˜³ð˜¶ð˜¯ð˜¤ð˜¢ð˜µð˜¢